Indian Subnational Finances : Recent Performance - Prasad, Ananthakrishnan (IMF Working Papers; Working Paper ;, 2007)
The fiscal performance of the States in India has been an area of concern for quite some time. The Twelfth Finance Commission (TFC) recommended a three-pronged strategy to alleviate States' fiscal distress, built around greater orientation toward market discipline, incentives for fiscal consolidation targets, and commitment to fiscal correction. We find that States have created fiscal space through raising revenues and reducing and reprioritizing expenditures. Looking ahead, expansion of fiscal space is essential to meet the States' large infrastructure and social needs in order to alleviate bottlenecks to growth. This needs to be accomplished without undermining fiscal sustainability.